Postcoloniality in Southeast Asia? - Lim, Shirley Geok-Lin (SARE: Southeast Asian Review of English, 2017)
When did Southeast Asia appear as a concept in geo-political imaginaries? Writing in the first half of the 1950s, the historian DGE Hall noted that the term became generally used only during WWII, to signify a land mass covering the "mainland states of Burma, Thailand, Laos, Cambodia, North and South Vietnam and Malaya together with the two great island groups... the Republic of Indonesia and the Republic of the Philippines. According to Hall, the term signified not so much a coherent region with unified forms of language, ethnicity, religion etc as one of simultaneous mixing and maintanence of local differences.